The Diagnostic Pathway of Hirschsprung's Disease in Paediatric Patients: A Single-Centre Experience - Annita Budzanowski; Niamh Geoghegan; Alexander Macdonald; Muhammad Choudhry (MDPI AG, 2024)
Background: The presenting symptoms of patients with Hirschsprung's disease (HD) are a failure to pass meconium, abdominal distension, and bilious vomiting. The gold standard diagnosis is a rectal biopsy to confirm aganglionosis. The aim of our study was to describe the diagnostic pathway of Hirschsprung's disease at our institution and document the indication for a rectal biopsy. Methods: We have performed a prospective collection of all patients who underwent a rectal biopsy to exclude HD from December 2022 until September 2023 including. The following data were collected: patient's age, presenting symptoms, type of biopsy, failure rate, complications, and histopathological results. Results: We identified 33 patients who underwent 34 rectal biopsies at 0.6 years of age. A total of 17 patients had a rectal suction biopsy (RSB), and 17 patients underwent a partial thickness under general anaesthesia (GA). 1/17 (6%) patients had an inconclusive RSB and subsequently underwent a biopsy under GA. Constipation and chronic abdominal distension plus vomiting were the most common presenting symptoms throughout all ages. Five patients (15%) had a rectal biopsy that was positive for HD. Conclusion: A protocolised approach to the assessment of infants and children with suspected HD ensures the appropriate utilisation of invasive procedures such as biopsy.